Perancangan Sistem Pakar Penyakit Gigi Menggunakan Metode Forward Chaining Pada Klinik Pratama Condet - Ahmad Ishaq; Hesti Nugraheni; Ahmad Al Kaafi; Eva Rahmawati; Nandang Iriadi; Achmad Sumbaryadi (LPPM Universitas Bina Sarana Informatika, 2020)
Teeth are hard parts in the mouth. The tooth has a varied structure that functions as a cutter, renderer and food chewer. If the tooth is not cleaned after eating, it can cause bacteria to appear. Where these bacteria can damage teeth and cause a person to get dental disease. In addition to teeth is a tool for digestion of food, teeth are also a person's appearance. This display is very much needed and someone needs to meet face to face with other people. When cavities, will automatically reduce one's appearance. Moreover, cavities are accompanied by toothache, this can interfere with one's activities in doing work. expert system which is an artificial intelligence program that combines the base of the knowledge base with an inference system to imitate an expert. It is also a system that seeks to adopt human knowledge to computers, so that computers can solve problems as is usually done by experts. Forward Chaining is a decision-making strategy that starts from the fact to the final conclusion. Then monitoring uses an internet connection to connect to the web.Key Word: Dental Disaese, Expert System, Forward Chaining, Web